Charge transport of novel blue dibenzothiophene phenylenediamine copolymer - Kar Y.B.; Abdullah S.F.; Chou Y.T.; Kok H.C. (2023)
We report the charge transport characteristics of dibenzothiophene phenylenediamine copolymer (DBT-PD). Fig. 1 shows DBT-PD (Mw = 77,000) which is a 50:50 molar ratio random copolymer consisting of DBT and a hole-transporting phenylenediamine group with tertiarybutyl substituents. The quoted ratio is of the starting monomers introduced into the reaction and may change slightly after polymerization due to differences in reactivity, possible side reactions and so on. Arylamine moieties of the type used here are extensively utilised in LED and photodetector materials due to their very good hole transport properties, low ionisation potentials (facilitating hole injection) and overall stability to oxidation [1]. They have been widely used in xerographic applications for many years. 2010 IEEE.